A Risk Analysis of Online Shopping Space: A Case of Saudi Arabia Post the Pandemic (Covid-19) - Nourah Alsuqayh, Soumayah Alghannam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
E-commerce has become a significant trend in the business with the emergence of digitalization, where businesses shifted their transactions to online platforms to take advantage of the global market. However, the universal rise of online transactions especially after the pandemic (Covid-19) due to lockdowns, comes with an expected rise in risks and challenges. This research aims to perform a risk analysis of online shopping in Saudi Arabia by examining three risk factors (financial, security, and product/service risks) that affect the online purchasing behavior of customers in Saudi Arabia. A questionnaire was used for data collection, and finally, a quantitative analysis was performed to test the risk behavior hypotheses. The questionnaire's findings showed that financial risk, product/service risk, and security risk have a significant negative impact on the intention to purchase (online). Therefore, online retailers in Saudi Arabia should develop strategies to minimize those risks, especially the perceived security risks as the results showed that it’s the highest “negatively” affecting factor in online shopping intentions